Changes in injury‐related hospital emergency department presentations associated with the imposition of regulatory versus voluntary licensing conditions on licensed venues in two cities. (26th February 2014) - Miller, Peter; Curtis, Ashlee; Palmer, Darren; Busija, Lucy; Tindall, Jennifer; Droste, Nicolas; Gillham, Karen; Coomber, Kerri; Wiggers, John
Abstract Introduction and Aims Regulatory and collaborative intervention strategies have been developed to reduce the harms associated with alcohol consumption on licensed venues around the world, but there remains little research evidence regarding their comparative effectiveness. This paper describes concurrent changes in the number of night‐time injury‐related hospital emergency department presentations in two cities that implemented either a collaborative voluntary approach to reducing harms associated with licensed premises (Geelong) or a regulatory approach (Newcastle). Design and Methods This paper reports findings from Dealing with Alcohol‐Related problems in the Night‐Time Economy project. Data were drawn from injury‐specific International Classification of Disease, 10th Revision codes for injuries (S and T codes) presenting during high‐alcohol risk times (midnight—5.59 am, Saturday and Sunday mornings) at the emergency departments in Geelong Hospital and Newcastle (John Hunter Hospital and the Calvary Mater Hospital), before and after the introduction of licensing conditions between the years of 2005 and 2011. Time‐series, seasonal autoregressive integrated moving average analyses were conducted on the data obtained from patients' medical records. Results Significant reductions in injury‐related presentations during high‐alcohol risk times were found for Newcastle since the imposition of regulatory licensing conditions (344 attendances per year, P < 0.001). None of the interventions deployed in Geelong (e.g. identification scanners, police operations, radio networks or closed‐circuit television) were associated with reductions in emergency department presentations. Discussion and Conclusions The data suggest that mandatory interventions based on trading hours restrictions were associated with reduced emergency department injury presentations in high‐alcohol hours than voluntary interventions. [Miller P, Curtis A, Palmer D, Busija L, Tindall J, Droste N, Gillham K, Coomber K, Wiggers J. Changes in injury‐related hospital emergency department presentations associated with the imposition of regulatory versus voluntary licensing conditions on licensed venues in two cities. Drug Alcohol Rev 2014;33:314–322]*